Eutherian-specific homeobox genes in the preimplantation embryo; function, evolution, and applications. - Royall, AH (2019)
This thesis explores the evolution, function, and possible applications of a group of lineage-specific genes known as the Eutherian Totipotent Cell Homeobox (ETCHbox) genes. The ETCHbox genes duplicated from a highly conserved vertebrate eye-specific homeobox gene called Cone-rod homeobox (CRX) in the lineage leading to eutherian mammals. The ETCHbox genes are unusual in many respects. Firstly, they are eutherian-specific, meaning that they are only present in the genomes of one group of mammals and not in marsupials or monotremes, which only have CRX. Secondly, they are highly variable in copy number and sequence, both compared to the “parental” gene from which they diverged, and between different species of eutherian mammal. Thirdly, their expression is limited to a few stages in the very early preimplantation embryo, after which they are not known to be expressed in any tissue. How can duplicates of a gene conserved in sequence and in function become so divergent so quickly, and what can their role be? I explore how the extreme divergence has evolved in eutherians, what their new functions could be, and whether their specificity for the very early embryo can be applied to the field of regenerative biology. I initially focus on the mouse genome, using ectopic expression to reveal unexpected functional overlaps between human and mouse paralogues, not orthologues, and hypothesise inferred ETCHbox function. I use sequence analysis and ectopic expression to explore the evolution of ETCHbox genes from CRX using comparisons of eutherian and marsupial homeobox genes and embryology, finding evidence for a nuanced subfunctionalisation occurring on the eutherian lineage between CRX and ETCHbox. I then continue the evolutionary approach specifically within the order Rodentia, where I find that stepwise gene losses and sequence divergences occurred. Finally, I examine the effect of ETCHbox genes on pluripotency before discussing a model for how ETCHbox complexities could evolve. Overall, I have used a blend of computational and experimental techniques to increase our understanding of ETCHbox gene evolution and function, before exploring potential applications.